Identifikasi Jenis Kerusakan Pada Perkerasan Kaku (Studi Kasus Ruas Jalan Soekarno-Hatta Bandar Lampung) - Susanto, Muhammad; Putra, Sasana; Diana, I Wayan (Universitas Lampung, 2016)
Bandar Lampung is one city that has a road network for the distribution of goods and services (national activities), ie at the Soekarno-Hatta Bandar Lampung. So that existing transport movement is strongly influenced by the existing pavement conditions on roads Soekarno-Hatta Bandar Lampung. In addition, the road pavement conditions also have an impact on the smooth traffic and safety as well as comfort for road users. This study aims to determine the type of damage and the value of the condition on the rigid pavement on roads Soekarno-Hatta Bandar Lampung along with solutions and workarounds. The method used for the assessment is the Pavement Condition Index (PCI). Based on study results, note the condition of rigid pavement on the road Soekarno-Hatta Bandar Lampung, namely: segment 1 = 79.50 (very good), segment 2 = 74.00 (very good), segment 3 = 76.92 (very good) , segment 4 = 83.88 (very good), segment 5 = 94.89 (perfect), segment 6 = 93.56 (perfect), segment 7 = 91.04 (perfect), segment 8 = 83.54 (very good), segment 10 = 92.17 (perfect), the segment 11 = 61.25 (good), the segment 12 = 77.71 (very good), the segment 13 = 88.41 (perfect) and the segment 14 = 84.52 (very good). Despite the rigid pavement condition index is still in good condition category even perfect, but at some point there is a sample unit has a PCI value <55 (fair). Based on the PCI, the treatment needs to be done only in the form of micro handling for each type of damage.. Keywords : distress type, severity level, PCI